2016
DOI: 10.1097/scs.0000000000002837
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Craniofacial Fractures

Abstract: This series of pediatric craniofacial fractures near consistently demonstrated oblique fracture patterns, in contrast to the typical adult fracture patterns described by LeFort. Pediatric craniofacial fractures are also at increased risk of GSFs. Understanding of these principles is fundamental to successful therapy in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…While younger children generally suffer from trauma due to lowintensity forces, such as falls, older children are more likely to be exposed to highintensity forces, such as those resulting from traffic accidents, be cause as they grow, their trauma profile becomes similar to that observed in adults. 4,7 In addition, when they are young, children are protected by their parents against harmful events. 3 Regarding the time and day of the week of traffic acci dents, the concentration of events in the evening and on weekends corroborates other findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While younger children generally suffer from trauma due to lowintensity forces, such as falls, older children are more likely to be exposed to highintensity forces, such as those resulting from traffic accidents, be cause as they grow, their trauma profile becomes similar to that observed in adults. 4,7 In addition, when they are young, children are protected by their parents against harmful events. 3 Regarding the time and day of the week of traffic acci dents, the concentration of events in the evening and on weekends corroborates other findings.…”
Section: Discussionmentioning
confidence: 99%
“…241 million individuals in 2016, and studies have shown that these ac cidents represent the main etiology of craniofacial trauma among children. 3,4 The consequences of trauma in the craniofacial region can include any combination of bone, soft tissue or dental injury. 5 The location and pattern of the injury depend on the interrelation between the etiology of the injury and the magnitude of the impact as well as on the character istics of the victim's developmental stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In contrast to facial fractures in adults, pediatric fractures present less predictability, with oblique and Greenstick fractures being more common, increasing their difficulty of diagnosis and management. 3,4 In patients less than 5 years of age, the most common mechanisms of facial fractures are falls (44%), motor vehicles incidents (25%) and interpersonal violence (25%), with variation due to social, cultural and environmental factors. 3,5 Pediatric patients diagnosed with facial fractures exhibit a higher injury severity, with midface fractures being associated with a depressed Glasgow Coma Score (GCS), intracranial hemorrhage, cervical spine injuries, longer length of hospitalization, longer time spent in an intensive care setting and commonly have concomitant injuries (58% of patients).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric craniofacial fractures display oblique fracture patterns, while typical adult fractures exhibit patterns described by LeFort. Pediatric craniofacial fractures are under higher risk of growing fractures (2). With increasing age, the proportion of craniofacial fractures in all pediatric fractures tends to increase (3).…”
Section: Introductionmentioning
confidence: 99%